2007
DOI: 10.1002/adma.200601828
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Morphologies and Topologies of π‐Conjugated Polymers from Thermally Reactive Polymer Blends

Abstract: Nano‐ and microstructured architectures of π‐conjugated polymers (see figure) are obtained by solution‐casting blends of poly(methyl methacrylate) (PMMA) and a conjugated polymer bearing solubilizing tetrahydropyranyl groups followed by thermally induced, solid‐phase deprotection of the conjugated polymer and subsequent dissolution of PMMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…This has been accomplished using two different approaches with either thermocleavable or acid‐cleavable side chains (Figure 3). 38, 39…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been accomplished using two different approaches with either thermocleavable or acid‐cleavable side chains (Figure 3). 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…The most recent developments in this research direction have largely been through the use of thermo‐cleavable tertiary esters, where the side chain is attached to the active conjugated polymer backbone through a heat‐labile ester bond. As illustrated in Figure 4, thermocleavage of poly[3‐(2‐methyl‐2‐hexyl)‐oxy‐carbonylbithiophene] (P3MHOCT) can proceed in two distinct steps with increasing temperature by initial removal of the solubilizing tertiary substituent, leaving a carboxylic‐acid‐substituted thiophene (P3CT), which upon further heating to around 300 °C will decarboxylate, leaving native PT 37, 39. The thermocleaved materials, P3CT and PT, are insoluble in all solvents and have demonstrated superior stability, compared with P3MHOCT, in photovoltaic devices.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Holdcroft et al demonstrated the fabrication of nano/microscale patterned films of polythiophenes bearing solubilizing and thermally cleavable groups (tertrahydropyranyl, THP), also making use of phase separation during spin-casting polymer blends of the electroactive polymer and a dielectric polymer (poly(methyl methacrylate) or PS). 24 In this case, the thermal elimination of THP groups in acidic medium enables the dielectric polymer to be washed away leaving an insoluble dot matrix of conjugated polymer. 24 We note that surface pattern-ordered phase separation was also already reported in spin-cast blends of CPs and PSs deposited on chemically patterned surfaces, representing a step forward in relation to the isotropic patterning approach, although more complicated procedures are involved.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37] Similarly, a related strategy has been employed to process conjugated polymers for use in OPV. [42][43][44][45] Chemical routes prot from high side chain cleavage efficiency. 38,39 Unfortunately, however, such alkyl chains have been shown to promote degradation.…”
Section: Introductionmentioning
confidence: 99%